2018
DOI: 10.1021/acs.jpclett.8b01054
|View full text |Cite
|
Sign up to set email alerts
|

Restoring Size Consistency of Approximate Functionals Constructed from the Adiabatic Connection

Abstract: Approximate exchange–correlation functionals built by modeling in a nonlinear way the adiabatic connection (AC) integrand of density functional theory have many attractive features, being virtually parameter-free and satisfying different exact properties, but they also have a fundamental flaw: they violate the size-consistency condition, crucial to evaluate interaction energies of molecular systems. We show that size consistency in the AC-based functionals can be restored in a very simple way at no extra compu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
115
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 37 publications
(115 citation statements)
references
References 59 publications
0
115
0
Order By: Relevance
“…However, it has been recently shown that this size consistency error can be easily corrected at no additional computational cost. 33 All these tests have concerned only the quality of the computed energies, whereas no information has been gathered on the XC potentials delivered by the functionals.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been recently shown that this size consistency error can be easily corrected at no additional computational cost. 33 All these tests have concerned only the quality of the computed energies, whereas no information has been gathered on the XC potentials delivered by the functionals.…”
Section: Introductionmentioning
confidence: 99%
“…Via (42), δF ZPE /δρ(x) indeed introduces a correction in the mid-bond region. In fact, since we have [42] f [ρ D ](x → 0 + ) ∼ log(x) − R + log 2 1 + e −R , (51) from our treatment in section III D, the divergence in the mid-bond region can be readily evaluated inserting (51) (52) For any fixed x = 0, we find δF ZPE /δρ D (R; x) → 0 as R → ∞ while similarly, due to the fact that ω(x) = ω f (x) , a divergence of the XC potential appears also at large x. Thus, the kinetic correlation energy introduced by the ZPE creates a divergence instead of a finite peak in the bond mid-point, and this divergence occurs on a region that shrinks when R → ∞.…”
Section: Exchange-correlation Potential For a 1d Dimermentioning
confidence: 99%
“…24,25 Mixing KS DFT with Hartree-Fock (HF) ingredients is an approximation strategy that has a long history in chemistry, already starting with hybrids 1-3,26-29 and double hybrids, 4-7 but also by simply inserting the HF density into a given approximate XC density functional. [30][31][32][33][34][35] Very recently, it has also been observed that rather accurate interaction energies, 36,37 particularly for noncovalent complexes, 38 can be obtained from models for W DFT λ [ρ] that interpolate between the two limits of Eq. (4) -retaining only the first term, GL2, in the GL series -and of Eq.…”
mentioning
confidence: 99%
“…To be more precise, −v H (r, [ρ]) is more attractive than the one-body potential v ∞ (r, [ρ]). In fact, the potential v ∞ (r, [ρ]), which has been studied in several works 21,[44][45][46] is generated by a charge that integrates to N − 1, 21,45…”
mentioning
confidence: 99%
See 1 more Smart Citation